In vitro transport of methotrexate by Drosophila Multidrug Resistance-associated Protein. - Agnes Karasik; András Váradi; Flóra Szeri (PLoS ONE, 2018)
Methotrexate (MTX) is a widely used chemotherapeutic agent, immune suppressant and antimalarial drug. It is a substrate of several human ABC proteins that confer multidrug resistance to cancer cells and determine compartmentalization of a wide range of physiological metabolites and endo or xenobiotics, by their primary active transport across biological membranes. The substrate specificity and tissue distribution of these promiscuous human ABC transporters show a high degree of redundancy, providing robustness to these key physiological and pharmacological processes, such as the elimination of toxins, e.g. methotrexate from the body. A similar network of proteins capable of transporting methotrexate has been recently suggested to exist in Drosophila melanogaster. One of the key players of this putative network is Drosophila Multidrug-resistance Associated Protein (DMRP). DMRP has been shown to be a highly active and promiscuous ABC transporter, capable of transporting various organic anions. Here we provide the first direct evidence that DMRP, expressed alone in a heterologous system lacking other, potentially functionally overlapping D. melanogaster organic anion transporters, is indeed able to transport methotrexate. Our in vitro results support the hypothesized but debated role of DMRP in in vivo methotrexate excretion.